Analysis of Challenges And Opportunities For The Development Of Syariah Cooperates In The Digital Era (Study of Sharia Cooperative Solution With Lamlhom) - Murni, Seri; Afdhalurrajul, Afdhalurrajul (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2025)
Digitalization also opens up new opportunities for Islamic cooperatives in developing products and services that are in line with Islamic law. Challenges also accompany the digitalization of Islamic cooperatives, such as data security and privacy risks. This study aims to analyze the challenges and opportunities for the development of the Lamlhom Islamic Cooperative in the digital era. The method used is a qualitative approach with field study research. The results of this study found that the main challenges include limited human resources, low digital literacy, infrastructure constraints, and the role of the Sharia Supervisory Board. However, digitalization enhances service efficiency, accelerates transactions, and attracts younger generations. The implementation of the USSI application supports accountable data management. Adaptation efforts are carried out through internal training and a hybrid system. Management support and member enthusiasm are important social capital in the digital transformation of Islamic cooperatives.